Styl současných teenagerů (na pozadi úvahy o "stylech vékových") - Hoffmanová, Jana (Stylistyka, 2000)
The style of children (and talking with children), as well as the style ofseniors (and talking with old people) are sometimes taken fort specific „age styles”. This article sum[1]marizes an analysis of another „age style”, style ofteenagers. Characteristic features of this style are humor, irony, play, show, exaggeration, and expressiveness. Boys live in an electronic (computerized) world and use its English terminology, but transform it into (Czech) slang. Intertextuality and informal conversation (even in written texts) belong to this style, too. The teenagers like old Czech and old phraseology; they play with word composition and abbreviations, with morphology and syntax; and they do not know much about Czech orthography. The analysis of this interesting „age style” gives us a picture of our young generation - and of the future of our life style.